Electronic structure of mesoionic compounds. The classification problem - Mariia Kyrpa; Sergiy Kovalenko; Volodymyr Ivanov (Вісник Харківського національного університету: Серія xімія)
Mesoionic compounds are conventionally categorized into two types based on the primary origin of electrons within the conjugated system, specifically determined by the arrangement of heteroatoms in the five-membered ring. An examination of diverse mesoionic compounds has been undertaken to address the pivotal query surrounding their classification: does the primary origin of electrons hold significance, and does this criterion demarcate a definitive boundary between the two types of compounds? To comprehensively address this issue, the DFT calculations were performed for a set of mesoionic molecules. The electronic properties of the molecules were studied within the frameworks of quantum theory of atoms in molecules (QTAIM) and the Nuclear Independent Chemical Shift (NICS).